Leadership In The Era Of Economic Uncertainty - "Charan, Ram." (New York)
"A toxic environment -- At the helm : what CEOs, business unit, and country managers must do -- On the front lines : sales and marketing -- Mind over money : the chief financial officer -- Making it all work : operations -- Refocusing innovation : research & development -- From supplies to sales : sourcing and distribution -- Supporting the team : staff functions -- The view from the top : the board of directors."
Keywords: LEADERSHIP.;FINANCIAL CRISES.;ACHIEVEMENT MOTIVATION